Combined effect of water loss and wounding stress on gene activation of metabolic pathways associated with phenolic biosynthesis in carrot - Becerra-Moreno, Alejandro; Redondo-Gil, Mónica; Benavides, Jorge; Nair, Vimal; Cisneros-Zevallos, Luis; Jacobo-Velázquez, Daniel A. (Frontiers in Plant Science, 2015)
Abstract: The application of postharvest abiotic stresses is an effective strategy to activate the primary and secondary metabolism of plants inducing the accumulation of antioxidant phenolic compounds. In the present study, the effect of water stress applied alone and in combination with wounding stress on the activation of primary (shikimic acid) and secondary (phenylpropanoid) metabolic pathways related with the accumulation of phenolic compound in plants was evaluated. Carrot (Daucus carota) was used as model system for this study, and the effect of abiotic stresses was evaluated at the gene expression level and on the accumulation of metabolites. As control of the study, whole carrots were stored under the same conditions. Results demonstrated that water stress activated the primary and secondary metabolism of carrots, favoring the lignification process. Likewise, wounding stress induced higher activation of the primary and secondary metabolism of carrots as compared to water stress alone, leading to higher accumulation of shikimic acid, phenolic compounds and lignin. Additional water stress applied on wounded carrots exerted a synergistic effect on the wound-response at the gene expression level. For instance, when wounded carrots were treated with water stress, the tissue showed 20- and 14-fold increases in the relative expression of 3-deoxy-D-arabino-heptulosanate synthase and phenylalanine ammonia-lyase genes, respectively. However, since lignification was increased, lower accumulation of phenolic compounds was detected. Indicatively, at 48 h of storage, wounded carrots treated with water stress showed 31% lower levels of phenolic compounds and 23% higher lignin content as compared with wounded controls. In the present study, it was demonstrated that water stress is one of the pivotal mechanism of the wound-response in carrot. Results allowed the elucidation of strategies to induce the accumulation of specific primary or secondary metabolites when plants are treated with water stress alone or when additional water stress is applied on wounded tissue. If the accumulation of a specific primary or secondary metabolite were desirable, it would be recommended to apply both stresses to accelerate their biosynthesis. However, strategies such as the use of enzymatic inhibitors to block the carbon flux and enhance the accumulation of specific compounds should be designed.